Do Big Inequalities in Executive Pay Hurt Firm Performance? - Richard Yiu-Ming Chung; Jed DeVaro; Scott Fung (Institute of Labor Economics (IZA), 2024)
Research Question/ Issue: Do large, within-firm executive pay differences hurt firm performance? Prior literature shows mixed results concerning the sign of the relationship between executive pay disparity and firm performance. This study evaluates that literature, clarifies what tournament theory predicts about the relationship, identifies methodological pitfalls and how to address them, and guides future scholarship in this area of considerable importance to firms and policy makers. Research Findings/ Insights: We estimate the relationship using improved methodology and find evidence of an inverted-U shaped relationship between the executive pay spread and firm performance. However, the peak of this inverted U occurs at such a high level of the executive pay spread that it is practically irrelevant in most firms. The inverted U is found using a market-based measure of firm performance, but not a returns-based measure (i.e., ROA). Theoretical/Academic Implications: This study addresses the theoretical and empirical limitations of the prior literature, thereby providing more credible estimates of the relationship between pay disparity and firm performance. Tournament theory offers a unified framework that can explain an inverted-U-shaped relationship between the executive pay spread and firm performance. Practitioner/Policy Implications: Our results should reduce public concerns that CEOs increase their own compensation to exorbitant levels, to the detriment of firm performance.
Keywords: G32; G39; J31; M12; 330; executive compensation; vertical pay disparity; firm performance; tournament theory; market structure